2017
DOI: 10.1007/s10681-017-1876-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of historical datasets to develop multi-trait selection models in processing tomato

Abstract: Multi-trait indices (MTI) weigh traits based on their importance to facilitate selection in plant and animal improvement. In animal breeding, economic values are used to develop MTIs. For vegetables, economic data valuing traits are rarely available. We posit that varieties with traits valued by growers and processors achieve higher market share and longer life span. Our objective was to develop MTIs predicting success of tomato varieties. Historical data for the California processing tomato industry from 1992… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…However, lower efforts seemed devoted to °Brix, fruit dry weight, total polyphenols, total fruit fresh weight and leaf angle, all traits that might be considered in the future breeding both to increase the marketable yield and fruit quality in processing tomato. Similar results were also reported by Liabeuf and Francis (2017), which suggested that fruit quality had less of an influence on cultivar success than yield.…”
Section: Future Breeding Efforts In Processing Tomatosupporting
confidence: 88%
“…However, lower efforts seemed devoted to °Brix, fruit dry weight, total polyphenols, total fruit fresh weight and leaf angle, all traits that might be considered in the future breeding both to increase the marketable yield and fruit quality in processing tomato. Similar results were also reported by Liabeuf and Francis (2017), which suggested that fruit quality had less of an influence on cultivar success than yield.…”
Section: Future Breeding Efforts In Processing Tomatosupporting
confidence: 88%
“…In fact, "BRIGADE" could be a possible candidate for future breeding programs in order to develop an elite genotype of processing tomatoes suitable for the OFS, reducing the actual gap in term of marketable yield with the CFS. Furthermore, as suggested by Liabeuf and Francis [35] and Ronga et al [17], °Brix should be considered in the future breeding programs in addition to effort to increase the marketable yield and other fruit quality traits such as color in processing tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be considered, the occurrence of constraints such as pleiotropy, linkage-drag, epistatic effects, and relationships with other beneficial traits. For example, introgressing soluble solids is often challenging due to inverse correlations with the yield [53]. Moreover, pleiotropic effects may occur between the fruit size and color [51].…”
Section: Future Prospects For Using S Habrochaites Ils In Tomato Brementioning
confidence: 99%